Composición de la flora del bosque aluvial inundable y la diversidad de aves en la desembocadura del Río Itaya en época de media creciente, Iquitos – Perú - Chávez Ramírez, Mónica Araceli (2024)
Observations of birds and identification of flora of the flooded alluvial forest at the mouth of the Itaya River were made during the period of average flooding, between October 2021 and February 2022, using the methodologies of canoe census, line transects, auditory recognition and counting of plants by plots. The results indicate that the composition of the flora is made up of 60 species distributed in 29 families, including woody trees (Euphorbiaceae, Fabaceae, Myrtaceae, Urticaceae and Vitaceae), shrubs (Malvaceae, Rubiaceae) and floating aquatic plants (Poaceae, Araceae, Cucurbitaceae). A total of 50 bird species were recorded, distributed in 13 Orders and 22 families, with the Passeriformes, Pelacaniformes, Psittaciformes and Accipitriformes being the most abundant and diverse in the area studied. It is concluded that the level of the water that floods the study area conditions the composition of the flora (herbaceous) and the diversity of birds in the flooded alluvial forest, giving way to different strata generated by the cycles of flooding and drainage of the waters of the Itaya River, offering various uses such as feeding, shelter and reproduction sites that are exploited by the birds recorded according to the ecological requirements of the species.